ST36 Acupuncture Alleviates the Inflammation of Adjuvant-Induced Arthritic Rats by Targeting Monocyte/Macrophage Modulation. (27th February 2021) - Yang, Fuming; Gong, Yinan; Yu, Nannan; Yao, Lin; Zhao, Xue; Hong, Shouhai; Wang, Shenjun; Chen, Bo; Xu, Yuan; Pang, Guangchang; Wang, Hui; Guo, Yongming; et al.
Abstract : Background . Rheumatoid arthritis (RA) is a chronic systemic chronic autoimmune disease characterized by the aggregation of immune cells and secretion of cytokines in the joint synovium, causing hyperblastosis and even bone destruction. Acupuncture has been proven effective in RA treatment. This study aimed to investigate the anti-inflammatory action of acupuncture, specifically, in relation to immune cell interactions and key mediators. Methods . Rats with adjuvant-induced arthritics (AIA) were treated with manual acupuncture (MA) at Zusanli (ST36). Joint edema and paw withdrawal latency were monitored to observe the effects on inflammation. The levels of 24 cytokines, chemokines, and growth factors in ankle joints during the treatment (on days 1, 7, 15, and 21) were detected by multiplex immunoassay. A bioinformatics analysis based on a directed weighted mathematical model was used to construct cell communication network diagrams and identify the key cells through calculation. The monocyte/macrophage polarization in inflamed joints was investigated by detecting M1- and M2-phenotypic populations and their related cytokines. Results . ST36 MA alleviated paw edema and upregulated the nociceptive threshold of AIA rats. Several innate and adaptive immune cytokines were dynamically regulated by MA, and MA-treated rats showed a significant improvement in symptoms compared with AIA rats by day 21. The immune cell-cell communication networks were intensified with the development of RA but were significantly reduced after treatment with MA. MA was found to specifically regulate monocytes/macrophages in inflamed ankle joints ST36 MA also inhibited M1-phenotype macrophages accompanied by decreased levels of IL-1 β . Conclusions . ST36 MA showed anti-inflammatory and analgesic effects as well as inhibition of immune cell communication networks in inflamed joints of AIA rats. Inhibiting the polarization of macrophages to the M1-phenotype in inflamed joints may be one of the key mechanisms of MA anti-inflammatory action. This research highlighted a systematic research paradigm for investigating mechanisms of acupuncture action.